2017
DOI: 10.1016/j.watres.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Robust planning of sanitation services in urban informal settlements: An analytical framework

Abstract: New types of sanitation services are emerging to tackle the sanitation crisis in informal settlements. These services link toilet facilities to semi-decentralized treatment plants via frequent, road-based transport of excreta. However, information for the planning of such sanitation services is scarce, and their future operating conditions are highly uncertain. The key questions of this paper are therefore: a) what are the drivers behind success or failure of a service-based sanitation system in informal settl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…Fears that a collection service will be unreliable could also pose a serious barrier to purchase. Our own research (Schmitt et al, 2016) has shown that it is possible to plan and optimize a collection service. But more research in this neglected area is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fears that a collection service will be unreliable could also pose a serious barrier to purchase. Our own research (Schmitt et al, 2016) has shown that it is possible to plan and optimize a collection service. But more research in this neglected area is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed in Section 1, a resource-recovering UDDT was chosen as a model for the BDT. Since a number of processes exist for medium-scale resource recovery from source-separated toilet waste (McConville et al, 2014), we propose a system for the safe manual collection and transport of source-separated feces and urine to a local resource-recovery plant serving about 1000 people (Schmitt et al, 2016). …”
Section: Design Principles Of the Blue Diversion Toilet And The Testimentioning
confidence: 99%
“…A sanitation system – compared to a sanitation technology – considers all components required for the adequate management of human wastes, such as storage, collection, transport, treatment, discharge or reuse at the following levels ( Zurbrügg and Tilley, 2009 ). Starting at the household level with waste generation, a system can include storage and potentially also treatment and reuse of all products such as urine, excreta, greywater, rainwater/stormwater or even solid waste ( Schmitt et al., 2017 ). However, problems can rarely be solved at the household level alone.…”
Section: What's Toilet Revolution?mentioning
confidence: 99%
“…And yet this also impacts urban life and society even as the core sanitation requirements for the sustainability of urban cities are not treated (Anastasiadis & Metaxas, 2013, Czischke et al, 2015Jewitt, 2011;Lehmann, 2010a;Parkinson et al, 2009). Most of the time people will avoid the subject of faeces and urine and tuck them away under less unsavoury concepts such as wastewater and solid waste management while the real concerns overrun our metropolitan areas, which then hinders the SDGs targets for inclusive, safe and resilient cities hinged on a resource-based paradigm (RBP) (Bai et al, 2016;Schmitt et al, 2017;UNDP, 2016).…”
Section: Special Considerations For Integrating Regensan Into Urban Rmentioning
confidence: 99%